2022
DOI: 10.1186/s42506-022-00108-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of effective communication-based care on the childbirth experience and satisfaction among primiparous women: an experimental study

Abstract: Background There is insufficient scientific evidence on the effect of communication skills of childbirth care providers on maternal childbirth experience and satisfaction. The present study aimed to determine the effect of communication-based care on the childbirth experience and satisfaction among primiparous women. Methods A total of 80 primiparous women participated in this experimental study who were randomly assigned into the intervention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Supportive communication was another important theme identi ed in this research. The research ndings of Shamoradifar et al (2022) showed that different communications during pregnancy facilitate this period, and providing care based on effective communication improves the sense of control and support during childbirth. It leads to a positive experience of and satisfaction with delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive communication was another important theme identi ed in this research. The research ndings of Shamoradifar et al (2022) showed that different communications during pregnancy facilitate this period, and providing care based on effective communication improves the sense of control and support during childbirth. It leads to a positive experience of and satisfaction with delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to a positive experience of and satisfaction with delivery. Effective communication between caregivers and pregnant women during delivery leads to a positive experience of childbirth through creating the ability of self-control (30) . Eddy et al ( 2021) also emphasized the important role of husband in supportive relationships during the perinatal period.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these concluded that, a woman’s control and participation in decision-making during childbirth is an important part of maternal care. The key to global health care reform is the shift towards more patient-centered care, including their involvement in decision-making [ 24 , 38 41 ], and an important aspect of care during childbirth is respect for women’s autonomy, that is, respect for their needs [ 10 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important issues raised in SDM during labor and childbirth is the mother's participation in choosing the type of labor analgesia. Most women are looking for a way to relieve labor pain, which seems to be very effective in their satisfactory experience of childbirth [10][11][12]. However, the knowledge of most women is very low about the various methods of labor pain relief and their benefits and harms in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Iran show that there is no effective and acceptable communication between staff and pregnant women in the maternity wards ( 16 , 17 ). Also, most Iranian mothers (75%) report one or more instances of non-respectful maternal care ( 18 ).…”
Section: Introductionmentioning
confidence: 99%